ASSESSMENT OF POST-HARVEST HANDLING ACTIVITIES AND MARKETING PATTERNS OF NON-TIMBER FOREST PRODUCTS BY RURAL WOMEN IN SOUTHWESTERN NIGERIA - BAMIWUYE , O. A.; ADISA , B. O.; ALAO , O. T.; AJAYI , F.O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
Non-Timber Forest Products (NTFPs) play an important role in the life of rural women and the economy of rural households in Nigeria. The study assessed the post-harvest handling activities and marketing patterns of non-timber forest products and identified the socioeconomic variables associated with post-harvest handling activities in the fringe communities of Southwestern Nigeria. Three States (Ondo, Osun and Ogun) were purposively selected from the six States in Southwestern Nigeria.  Data were collected from 320 respondents from 32 communities out of 158 in Omo, Oluwa, Akure-Ofosu and Shasha Forest Reserves using both structured and unstructured interview guides. Results on marketing patterns showed that 68.1% of the respondents used the nearest town market; 47.2%  home sales; 40.6%  in informal local markets; 24.4% used the roadside and 22.5% used the door-to-door channel. The majority (73.1%) of the respondents reported no organised marketing arrangement for their products. A majority (83.1%) used no specialized storage facilities and 89.4% did not carry out any value addition before selling their products. Results of the binary logistic regression showed that age (Z=2.6, p<0.05), marital status (Z=-3.5, p<0.01), number of dependants (Z=-3.42, p<0.01), ownership of land (Z=-2.57, p<0.05), and number of children (Z=-2.5, p<0.05) were significantly related to post-harvest handling activities.  The study concluded that most women do not have an organised market for their NTFPs business and most do not add value to the NTFPs collected. We thus recommended that Government and private institutions/NGOs should provide a centralised modern market and specialized storage facilities to prevent the wastage of certain NTFPs which could have been converted to money.